Próba oceny podazy bialka w diecie u plywaków ze Szkól Mistrzostwa Sportowego w okresie treningu przygotowawczego - Przybylsi, S.; Matuszkiewicz, A.; Popinigis, J. (Medycyna sportowa, 2000)
Urea was determined in 24 h urine collected from 10 male and 15 female students of sport mastership schools aged 14-19 years. All subjects were competitive swimmers, their daily training volume amounting 4-6 h. Based on the assumption that the subjects were in nitrogen balance and that about 78% of urea was excreted, daily protein intake was assessed from urea determinations conducted twice, one month apart. In the first examination, 3 subjects had an estimated protein intake above 1,4 g/kg body mass. This included one subject with protein intake of 1,7 g/kg and another one - over 2 g/kg. In the second examination, 7 subjects had protein intake above 1,4 g/kg, including 4 subjects having protein intake between 1,7 and 1,9 g/kg. No subject had protein intake above 2 g/kg. When comparing the observed intake values with the recommended ones for endurance athletes (1,4 g/kg), speed-trained athletes (1,7 g/kg) or strength athletes (2,0 g/kg), a high frequency of insufficient protein intake can be stated. In conclusion, the group of 25 swimmers exhibited a too low protein intake as compared with the recommended amounts.